Investigation on aerodynamic force nonlinear evolution for a central-slotted box girder under torsional vortex-induced vibration - Liu, Shengyuan; Zhao, Lin; Fang, Genshen; Hu, Chuanxin; Ge, Yaojun (Journal of fluids and structures, 2021)
Central-slotted box girders are widely employed in long-span bridges owing to their advantageous flutter stability. However, the existence of a central slot can degrade their performance under vortex-induced vibrations (VIVs). To clarify the aerodynamic characteristics of a typical central-slotted box girder during VIVs, sectional model wind tunnel tests involving the synchronous measurement of pressure distributions and VIV responses were performed. The computational fluid dynamics (CFD) technique was also used to demonstrate the flow pattern development during VIV before qualitatively explaining the VIV mechanism of the central-slotted box girder. The surface pressure distributions at various amplitude-dependent VIV stages were measured and examined. The evolution of the aerodynamics was investigated from the perspective of the work done by the vortex-excited force (VEF). It was found that the aerodynamic effects on a central-slotted box girder during VIVs are featured with apparent nonlinear evolutionary characteristics. During the lock-in period, the wind-induced pressures at both upper and lower surfaces of the downstream box and the pressures at upper surface of the upstream box make greater contributions to the VEF, which are the main excitation sources of the torsional VIV. However, the contributions of the downstream and upstream boxes are opposite, showing positive and negative correlations with the VEF, respectively. It demonstrated that the positive contribution of the pressures at both upper and lower surfaces of the downstream box weakens the VIV performance of the central-slotted box girder as compared with a streamlined box girder. In addition, the central slot, which improves the correlating flow between the upper and lower regions around the downstream box, causes the distributed aerodynamic forces in these regions to enhance the VEF and perform positive work. This provides a reasonable explanation as to why the VIV effects of central-slotted box girders are typically stronger than those of streamlined box girders. •Torsional VIV characteristics of a central-slotted box girder is analyzed.•Aerodynamic evolution during VIV is discussed by wind tunnel test and CFD simulation.•The mechanism of torsional VIV for a central-slotted box girder is examined.•Reasonable explanation for weak VIV performance of central-slotted box girders.